Linnaeus' restless system: translation as textual engineering in eighteenth-century botany. - Dietz, Bettina (Annals of Science, 2016)
In this essay, translations of Linnaeus'Systema naturaeinto various European languages will be placed into the context of successively expanded editions of Linnaeus' writings. The ambition and intention of most translators was not only to make theSystema naturaeaccessible for practical botanical use by a wider readership, but also to supplement and correct it, and thus to shape it. By recruiting more users, translations made a significant contribution to keeping theSystemaup to date and thus maintaining its practical value for decades. The need to incorporate countless additions and corrections into an existing text, to document their provenance, to identify inconsistencies, and to refer to relevant observations, descriptions, and illustrations in the botanical literature all helped to develop and refine techniques of textual montage. This form of textual engineering, becoming increasingly complex with each translation cycle, shaped the external appearance of new editions of theSystema, and reflected the modular architecture of a botanical system designed for expansion.